Improved Enzymatic Hydrolysis of Pilot Scale Pretreated Rice Straw at High Total Solids Loading - Agrawal, Ruchi; Bhadana, Bharti; Mathur, A. S.; Kumar, Ravindra; Gupta, Ravi P.; Satlewal, Alok (Frontiers in Energy Research, 2018)
Enzymatic hydrolysis at high solids has potential to reduce both capital and operational expenditures. Here, dilute acid pretreatment of rice straw was carried out at on pilot scale (250 kg per day) at 162°C for 10 min and 0.35% acid concentration followed by enzymatic hydrolysis at different total solids loading. It showed that although total sugar concentration increased from 48 g/l to 132 g/l but glucan conversion reduced by 27% (84% to 66.2%) with increasing solids from 5% to 20% in batch mode. Therefore, two different fed-batch approaches were evaluated to improve the glucan conversion via sequential addition of substrate and/or enzyme. The maximum glucan conversion obtained in batch mode (Control) was only 61% and 66% after 24 h and 30h, respectively at 3 FPU enzyme/g solids while, 65% and 70% conversion was achieved at similar time and conditions by adding substrate in three batches of 50%, 25%, 25% at an interval of 0h, 4h, 8h respectively. Addition of surfactant (Ecosurf E6) further improved the conversion to 72% after 30h. The role of critical factors i.e. inhibitors, enzyme-lignin binding and viscosity was investigated during the course of hydrolysis in batch and fed-batch approaches. This study suggests a sustainable approach for improved hydrolysis at high solids by simple process fine-tunings.